Correction: Controlling CO2 hydrogenation selectivity by Rh-based catalysts with different crystalline phases of TiO2. Issue 16 (10th February 2023) - Cao, Fenghai; Gong, Nana; Ma, Zixuan; Wang, Xiaoxing; Tan, Minghui; Wu, Yingquan; Tan, Yisheng
Abstract : Correction for 'Controlling CO2 hydrogenation selectivity by Rh-based catalysts with different crystalline phases of TiO2 ' by Fenghai Cao et al., Chem. Commun., 2022, 58, 4219–4222, ; https://doi.org/10.1039/D2CC00472K .